The educational impact of the Covid-19 rapid response on teachers, students, and families: Insights from British Columbia, Canada - MacDonald, Margaret (Prospects (Paris), 2021)
The government’s rapid response to the spread of Covid-19 in British Columbia has resulted in drastic and unprecedented changes to the delivery of K-12 education. Using qualitative research methods, including remote in-depth interviews, this article addresses the question: What is the educational impact of the Covid-19 rapid response on teachers, students, and families in the Lower Mainland of British Columbia, Canada? Six themes are discussed, including teacher and family responses to change, vulnerability, transitions, work/home life balance, holistic teaching practices and communication. The article ends with recommendations relating to the communication and implementation of health, care, and educational practices that better attend to vulnerable populations and address social emotional wellness.